Intracellular signaling mechanisms of the melanocortin receptors: current state of the art - Rodrigues, A. (2015)
The melanocortin system is composed by the agonists adrenocorticotropic hormone and alpha, beta and gamma-melanocyte-stimulating hormone, and two naturally occurring antagonists, agouti and agouti-related protein. These ligands act by interaction with a family of five melanocortin receptors (MCRs), assisted by MCRs accessory proteins (MRAPs). MCRs stimulation activates different signaling pathways that mediate a diverse array of physiological processes, including pigmentation, energy metabolism, inflammation and exocrine secretion. This review focuses on the regulatory mechanisms of MCRs signaling, highlighting the differences among the five receptors. MCRs signal through G-dependent and independent mechanisms and their functional coupling to agonists at the cell surface is regulated by interacting proteins, namely MRAPs and beta-arrestins. The knowledge of the distinct modulation pattern of MCRs signaling and function may be helpful for the future design of novel drugs able to combine specificity, safety and effectiveness in the course of their therapeutic use.